2022
DOI: 10.1108/jed-03-2021-0035
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between FDI, host country characteristics and economic growth? A new panel evidence from BRICS

Abstract: PurposeThis study aims to assess the impact of foreign direct investment (FDI) on growth in presence of host country characteristics, namely, economic stability, human capital, financial development and trade openness, in the fastest emerging Brazil, Russia, India, China, South Africa (BRICS) economies, considered to be significant FDI destinations.Design/methodology/approachThe panel data for the variables under study, collected from World Investment Reports published by World Bank, are analyzed using feasibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…This analysis technique is appropriate for hypotheses with interaction impacts [56,[63][64][65]. In addition, Model 4 and Model 6 of the PROCESS macro approach, with 5000 bias-corrected bootstrapping samples [57,58,66,67], were used to examine mediate and moderate effects, respectively. To ensure the reliability of the analysis results, several demographic variables, such as gender, age, educational level, and monthly income, were also controlled as covariates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis technique is appropriate for hypotheses with interaction impacts [56,[63][64][65]. In addition, Model 4 and Model 6 of the PROCESS macro approach, with 5000 bias-corrected bootstrapping samples [57,58,66,67], were used to examine mediate and moderate effects, respectively. To ensure the reliability of the analysis results, several demographic variables, such as gender, age, educational level, and monthly income, were also controlled as covariates.…”
Section: Discussionmentioning
confidence: 99%
“…In a long-term-oriented culture, individuals will be willing to take actions that they find inconvenient, such as turning off the lights and air-conditioner, for a better future for themselves and their community [65]. Furthermore, in the field of sustainability, previous studies have demonstrated that long-term orientation is related to attitudes toward pro-social behaviours [66], pro-environmental intentions and behaviours [67], and even promoting the translation from pro-social attitudes and intentions into actual pro-social behaviours [68].…”
Section: Moderation Effectsmentioning
confidence: 99%
“…Attitudes refer to how a person consider something and tends to act towards it, often in an evaluative way [ 13 , 20 ]. Theory of planned behavior [ 21 ] argue that attitude towards behavior is the best predictor of behavioral intentions.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…Indeed, a number of prior studies, which applied the theory of planned behavior in their hypothesized frameworks, also reported that attitudes towards behaviors is determined as the most influential antecedents of behavioral intentions [ 21 , 22 , 23 ]. In the research area of COVID-19 vaccine acceptance, some previous studies also revealed that individuals’ attitudes towards COVID-19 vaccines was found to be positively related to their intentions to receive COVID-19 vaccines [ 20 ]. In the context of Vietnam, it is hypothetical that attitudes towards COVID-19 vaccines play the crucial role in predicting intentions to receive COVID-19 vaccines among Vietnamese adults.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…This variable is the most commonly used proxy for economic development and growth. According to Joo, Shawl, and Makina (2022), economic growth leads to an increase in a country's wage inequality if the economic development leads to an increase in the demand for skills. On the other hand, economic growth can lead to a reduction in wage inequality if policies are employed to increase the supply of skills or establish an imperfect wage competition mechanism (policies to protect regulations, minimum wage regulations, effective wage models, etc.).…”
Section: 𝑊𝐼 = 𝐴𝑣𝑒𝑟𝑎𝑔𝑒 𝑠𝑎𝑙𝑎𝑟𝑦 𝑜𝑓 𝑠𝑘𝑖𝑙𝑙𝑒𝑑 𝑤𝑜𝑟𝑘𝑒𝑟𝑠 𝐴𝑣𝑒𝑟𝑎𝑔𝑒 𝑠𝑎𝑙𝑎𝑟𝑦 𝑜𝑓 𝑢𝑛𝑠...mentioning
confidence: 99%